Pension System Methodology For Senior Citizens - NEGRU, Titel (Annals of Spiru Haret University. Economic Series, 2016)
The need to reform pension systems is one of the key social challenges for policymakers in Europe. The demographic evolutions of the last 26 years, the changes in the Romanian economy and society influenced one particular category - the retired people. As population inactive, retired people represents important year category, their numbers being rather big in comparison with the population employed, the practical pensions contributors are at the bottom with their founds.